Impact of active root zone soil potassium levels on cotton yield and fiber quality under no tillage - Shao, Jingjing; Liu, Aizhong; Dong, Helin; Li, Pengcheng; Sun, Miao; Feng, Weina; Huo, Feichao; Zheng, Cangsong (Frontiers in Plant Science, 2024)
Introduction Potassium deficiency significantly hinders cotton growth and development, adversely affecting yield and fiber quality. Applying potassium fertilizer is a common practice to address potassium deficiency in the soil. However, the effectiveness of potassium fertilizer application depends on the appropriate soil potassium levels in cotton fields. Methods This study used a randomized block design with six different soil potassium levels and conducted experiments across 18 micro-zones in the field. This study aimed to investigate the response of cotton yield and quality to different soil potassium levels, to try to clarify the suitable soil potassium levels for cotton growth, so as to provide practical and effective help for determining the amount of potash fertilizer in the cotton field. Results The results showed that the seedcotton yield was increasing, with the soil potassium level increased under no tillage. There was no significant difference among K4, K5, and K6 on seedcotton yield, which were significantly higher than K1 and K2. As soil potassium levels increased, the proportion of autumn boll and the proportion of outer boll also increased, indicating that higher soil potassium levels support the better growth and development of cotton in the middle and late stages, leading to increased boll sets and higher yields. Additionally, the available potassium content in the 0–40-cm soil layer was significantly correlated with yield and yield parameters but not with fiber quality indices. Discussion It is concluded that K4 treatment could provide sufficient potassium to meet the growth and development needs of cotton. Potassium fertilizer application is recommended when the available potassium content in the 0–40-cm soil layer falls below 122.88 mg kg-1 in the cotton field.